Illumination of parainfluenza virus infection and transmission in living animals reveals a tissue-specific dichotomy. - Crystal W Burke; John N Mason; Sherri L Surman; Bart G Jones; Emilie Dalloneau; Julia L Hurwitz; Charles J Russell (PLoS Pathogens)
The parainfluenza viruses (PIVs) are highly contagious respiratory paramyxoviruses and a leading cause of lower respiratory tract (LRT) disease. Since no vaccines or antivirals exist, non-pharmaceutical interventions are the only means of control for these pathogens. Here we used bioluminescence imaging to visualize the spatial and temporal progression of murine PIV1 (Sendai virus) infection in living mice after intranasal inoculation or exposure by contact. A non-attenuated luciferase reporter virus (rSeV-luc(M-F*)) that expressed high levels of luciferase yet was phenotypically similar to wild-type Sendai virus in vitro and in vivo was generated to allow visualization. After direct intranasal inoculation, we unexpectedly observed that the upper respiratory tract (URT) and trachea supported robust infection under conditions that result in little infection or pathology in the lungs including a low inoculum of virus, an attenuated virus, and strains of mice genetically resistant to lung infection. The high permissivity of the URT and trachea to infection resulted in 100% transmission to naïve contact recipients, even after low-dose (70 PFU) inoculation of genetically resistant BALB/c donor mice. The timing of transmission was consistent with the timing of high viral titers in the URT and trachea of donor animals but was independent of the levels of infection in the lungs of donors. The data therefore reveals a disconnect between transmissibility, which is associated with infection in the URT, and pathogenesis, which arises from infection in the lungs and the immune response. Natural infection after transmission was universally robust in the URT and trachea yet limited in the lungs, inducing protective immunity without weight loss even in genetically susceptible 129/SvJ mice. Overall, these results reveal a dichotomy between PIV infection in the URT and trachea versus the lungs and define a new model for studies of pathogenesis, development of live virus vaccines, and testing of antiviral therapies.